Motivators of United Kingdom Youth Tourists and their - Kirkpatrick, Stephen Craig (My University, 2011)
Youth tourism is a large growing global phenomena and potentially lucrative to South Africa. This research undertook to determine travel motivators of United Kingdom youth tourists and perceptions of South Africa as a youth tourist destination, hoping this would assist in developing the South African youth tourist product. Self administered questionnaires were completed and data analysed using descriptive statistics, Students t-tests and ANOVA tests. Results were used to address the propositions, sub-problems and research problem. Findings suggest that travel motivators of UK youth tourists are experience seeking, sociability and relaxation seeking, and that UK youth tourists are noninstitutionalised and independent tourists, preferring new and exotic destinations. The research revealed that South Africa is perceived as a country with environmental splendour, is potentially dangerous (this did not dissuade UK youth tourists) and an expensive destination. Findings have implications on developing the South African youth tourist destination and marketing this product effectively
MBA - WBS
Keywords: Tourism; Motivation; Youth tourism